Analysis of Selected Solutions of Drive Systems and Steering Devices Used on Port Loaders - Marut, T. (Scientific Journal of Gdynia Maritime University, 2018)
The article analyzes the propulsion systems i.e. of the port tug and shows the advantages and disadvantages of the propeller described fixed-pitch screw, variable pitch screw, nozzle screw, azimuthal propeller, cycloidal propeller, Doerffer’s Rudder.